Polarizing film, polarizing plate, and method for producing polarizing film

By using a polyvinyl alcohol-based resin film with dichromatic substances in the polarizing film, combined with multi-stage stretching and drying shrinkage treatment, the problem of warping of the polarizing film in the absorption axis direction is solved, and excellent bending and Stability, suitable for thinner image display devices.

CN119247533AActive Publication Date: 2025-01-03NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411316184.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-02-26
Filing Date
2020-02-18
Publication Date
2025-01-03
Estimated Expiration
2040-02-18

AI Technical Summary

Technical Problem

The existing polarizing films are prone to warping in the absorption axis direction, and are particularly obvious in organic electroluminescent display devices, which affects the stability of the device and the image display effect.

Method used

A polyvinyl alcohol-based resin film containing dichromatic substances was used, and the shrinkage ratio of the absorption axis direction and the orthogonal direction after being placed at 85°C for 120 hours was 0.5 to 1.5, combined with air-assisted stretching and water-in-lengthing The total stretching ratio was adjusted to 3.0 to 4.0 times, and the width direction was shrinked by drying and shrinking treatment to be 2% or more to form a polarizing film with a thickness of 8 μm or less.

Benefits of technology

The warping of the absorption axis direction of the polarizing film is significantly suppressed, and its bending properties are improved. It is suitable for thinner image display devices, especially organic EL display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119247533A_ABST
    Figure CN119247533A_ABST
Patent Text Reader

Abstract

Provided is a polarizing film in which warpage in the absorption axis direction is suppressed and which has excellent bending properties. The polarizing film according to the present invention is composed of a polyvinyl alcohol resin film containing iodine, and the ratio SMD / STD of the shrinkage rate SMD in the absorption axis direction after the polarizing film is left at 85 DEG C for 120 hours to the shrinkage rate STD in the direction orthogonal to the absorption axis direction is 0.5-1.5. In one embodiment, the thickness of the polarizing film is 8 [mu] m or less. A polarizing plate according to the present invention comprises the polarizing film and a protective layer disposed on at least one side of the polarizing film.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of February 18, 2020, application number 202080016060.6, and invention name “Polarizing film, polarizing plate, and method for manufacturing the polarizing film”. Technical Field

[0002] The present invention relates to a polarizing film, a polarizing plate, and a method for manufacturing the polarizing film. Background Art

[0003] In a liquid crystal display device, which is a representative image display device, polarizing films are arranged on both sides of the liquid crystal unit due to its image formation method. As a method for manufacturing a polarizing film, for example, the following method has been proposed: a laminate having a resin substrate and a polyvinyl alcohol (PVA) resin layer is stretched, and then a dyeing treatment is performed to obtain a polarizing film on the resin substrate (for example, Patent Document 1). Using such a method, a thin polarizing film can be obtained, and therefore it has attracted attention as a method that contributes to the thinning of image display devices in recent years. However, the thin polarizing film as described above has the problem of being easily warped in the absorption axis direction. Such a problem is more obvious when a thin polarizing film is applied to an organic electroluminescent (EL) display device. Specifically, since the organic EL display device itself is thin and a polarizing film (essentially a polarizing plate) is only arranged on one side of the device, the warping of the device becomes obvious.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-343521 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polarizing film having suppressed warping in the absorption axis direction and excellent bendability.

[0009] Solutions for solving problems

[0010] The polarizing film of the present invention is composed of a polyvinyl alcohol-based resin film containing a dichroic substance, and the shrinkage rate S in the absorption axis direction of the polarizing film after being left at 85° C. for 120 hours is MD The shrinkage rate S in the direction perpendicular to the absorption axis direction TD The ratio of S MD / S TD It is 0.5 to 1.5.

[0011] In one embodiment, the polarizing film has a thickness of 8 μm or less.

[0012] In one embodiment, the polarizing film has a single body transmittance of 40.0% or more and a degree of polarization of 99.0% or more.

[0013] In one embodiment, the shrinkage ratio S in the absorption axis direction is MD and the shrinkage rate S in the direction perpendicular to the absorption axis direction TD They are less than 0.4% respectively.

[0014] In one embodiment, the orientation function of the polarizing film is 0.30 or less.

[0015] According to another aspect of the present invention, a polarizing plate is provided, comprising: the polarizing film described above, and a protective layer disposed on at least one side of the polarizing film.

[0016] According to another aspect of the present invention, a method for manufacturing the above-mentioned polarizing film is provided. The manufacturing method comprises: forming a polyvinyl alcohol resin layer containing iodide or sodium chloride and polyvinyl alcohol resin on one side of a long strip of thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%. The total stretching ratio of the air auxiliary stretching treatment and the underwater stretching treatment is 3.0 to 4.0 times relative to the original length of the laminate; the stretching ratio of the air auxiliary stretching treatment is greater than the stretching ratio of the underwater stretching treatment.

[0017] Effects of the Invention

[0018] According to the present invention, by optimizing the ratio of the shrinkage rate in the absorption axis direction to the shrinkage rate in the direction orthogonal to the absorption axis direction, a polarizing film in which the warping in the absorption axis direction is suppressed can be obtained. The optimization of the shrinkage rates in the above two directions can be achieved in a polarizing film obtained by a manufacturing method that combines air auxiliary stretching and underwater stretching and adjusts their stretching ratios, and reduces the total stretching ratio. Furthermore, in one embodiment, by setting the thickness of the polarizing film to a specified value (e.g., 8 μm) or less, a polarizing film with excellent bendability can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.

[0020] Figure 2 This is a schematic diagram showing an example of a drying shrinkage process using a heating roller. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0022] A.Polarizing film

[0023] The polarizing film of the embodiment of the present invention is composed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance (representatively, iodine or a dichroic dye), and the shrinkage rate S in the absorption axis direction of the polarizing film after being left at 85° C. for 120 hours is MD The shrinkage rate S in the direction perpendicular to the absorption axis direction (hereinafter sometimes referred to as the transmission axis direction) is TD The ratio of S MD / S TD is 0.5 to 1.5. That is, the anisotropy of thermal shrinkage of the polarizing film of the embodiment of the present invention is significantly small. Hereinafter, in this specification, such characteristics related to thermal shrinkage are sometimes referred to as "isotropic shrinkage". With such a structure, the warping of the polarizing film in the absorption axis direction can be significantly suppressed. Such a polarizing film (resulting in a polarizing plate) can be suitably applied to an organic EL display device. Since the organic EL display device is thin and has a polarizing film (essentially a polarizing plate) only on one side, the warping of the device is large, but using such a polarizing film can significantly suppress the warping. Compared with S MD / S TD It is preferably 0.7 to 1.3, more preferably 0.8 to 1.2, further preferably 0.9 to 1.1, and particularly preferably 0.94 to 1.16.

[0024] Shrinkage rate in the absorption axis direction S MD The shrinkage ratio S in the transmission axis direction is preferably 0.4% or less, more preferably 0.3% or less, and still more preferably 0.2% or less. TD For example, it is 0.42% or less, preferably 0.4% or less, more preferably 0.3% or less, and further preferably 0.2% or less. MD and S TD The smaller the better, and ideally zero. The polarizing film of the embodiment of the present invention not only has isotropic shrinkage, but also has small shrinkage in the absorption axis direction and the transmission axis direction. As a result, warping can be further suppressed. It should be noted that when the polarizing film is typically provided as a component of a polarizing plate or a polarizing plate with an adhesive layer, S MD and S TD The polarizing plate protective layer and / or adhesive layer may be changed according to the type and / or characteristics. MD / S TD Regardless of the type and / or characteristics of the protective layer and / or adhesive layer, a certain range can be maintained substantially.

[0025] The thickness of the polarizing film is preferably 8 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, particularly preferably 3 μm or less, and particularly preferably 2 μm or less. The lower limit of the thickness of the polarizing film may be, for example, 1 μm. The thickness of the polarizing film may be 2 μm to 6 μm in one embodiment, 2 μm to 4 μm in another embodiment, 2 μm to 3 μm in another embodiment, 5 μm to 7.5 μm in another embodiment, and 5.5 μm to 7 μm in another embodiment. By making the thickness of the polarizing film very thin in this way, the shrinkage rate in the absorption axis direction and the shrinkage rate in the transmission axis direction can be made very small. Furthermore, by making the thickness of the polarizing film very thin in this way, a polarizing film with excellent bendability can be obtained. As a result, a polarizing film that can be applied to a preferably curved image display device, a more preferably bendable image display device, and a more preferably foldable image display device can be obtained.

[0026] The polarizing film preferably shows absorption dichroism at any wavelength in the wavelength range of 380nm to 780nm. The monomer transmittance of the polarizing film is preferably 40.0% or more, more preferably 41.0% or more. The upper limit of the monomer transmittance can be, for example, 49.0%. The monomer transmittance of the polarizing film is 40.0% to 45.0% in one embodiment. The polarization degree of the polarizing film is preferably 99.0% or more, more preferably 99.4% or more. The upper limit of the polarization degree can be, for example, 99.999%. The polarization degree of the polarizing film is 99.0% to 99.99% in one embodiment. According to the present invention, although the total stretching ratio in the manufacture of the polarizing film is very small as described later, such a practically acceptable monomer transmittance and polarization degree can be achieved. It is speculated that this is because of the manufacturing method described later. It should be noted that the monomer transmittance is representatively the Y value obtained by measuring using an ultraviolet visible spectrophotometer and performing visual sensitivity correction. The single transmittance is a value when the refractive index of one surface of the polarizing plate is converted to 1.50 and the refractive index of the other surface is converted to 1.53. The polarization degree is typically obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc obtained by measuring with an ultraviolet visible spectrophotometer and performing sensitivity correction.

[0027] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0028] The orientation function of the polarizing film is, for example, less than 0.30, and for example, less than 0.25, preferably less than 0.22, more preferably less than 0.20, further preferably less than 0.18, and particularly preferably less than 0.15. When the orientation function is in such a range, the desired isotropic shrinkage can be achieved. The lower limit of the orientation function can be, for example, 0.05. If the orientation function is too small, sometimes an acceptable monomer transmittance and / or polarization degree cannot be obtained.

[0029] The orientation function (f) can be obtained, for example, by using a Fourier transform infrared spectrometer (FT-IR) and attenuated total reflection (ATR) measurement with polarized light as the measurement light. Specifically, the measurement is carried out in a state where the stretching direction of the polarizing film is parallel and perpendicular to the polarization direction of the measurement light, and the 2941 cm-1 absorbance spectrum is used. -1 The intensity I is calculated by the following formula. Here, the intensity I is based on 3330cm -1 The reference peak is 2941cm -1 / 3330cm -1 It should be noted that when f = 1, it is completely oriented, and when f = 0, it is random. In addition, it is considered that 2941cm -1 The peak is due to the absorption of the vibration of the main chain (-CH2-) of PVA in the polarizing film.

[0030] f=(3 <cos 2 θ>-1) / 2

[0031] =(1-D) / [c(2D+1)]

[0032] =-2×(1-D) / (2D+1)

[0033] in,

[0034] c=(3cos 2 β-1) / 2,2941cm -1 In the case of vibration, β = 90°.

[0035] θ: Angle of the molecular chain relative to the stretching direction

[0036] β: Angle of the transition dipole moment relative to the molecular chain axis

[0037] D=(I ⊥ ) / (I / / ) (In this case, the more oriented the PVA molecules are, the larger D becomes)

[0038] I ⊥ :Measure the absorption intensity when the polarization direction of light is perpendicular to the stretching direction of the polarizing film

[0039] I / / :Measure the absorption intensity when the polarization direction of light is parallel to the stretching direction of the polarizing film

[0040] The polarizing film is composed of a PVA-based resin film containing iodine as described above. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially a polarizing film) contains a PVA-based resin modified by acetoacetyl. When it is such a structure, a polarizing film with a desired puncture strength can be obtained. When the PVA-based resin as a whole is set to 100% by weight, the blending amount of the PVA-based resin modified by acetoacetyl is preferably 5% to 20% by weight, more preferably 8% to 12% by weight. When the blending amount is in such a range, the puncture strength can be set to a more appropriate range.

[0041] The polarizing film can be typically made using a laminate of more than two layers. As a specific example of a polarizing film obtained using a laminate, there can be cited a polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate. The polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate can be made, for example, as follows: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizing film. In the present embodiment, it is preferred that a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching preferably also includes stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is, for example, 3.0 to 4.5 times, which is significantly smaller than the usual ratio. Even with such a total stretching ratio, a polarizing film with acceptable optical properties can be obtained by combining the addition of a halide and a drying shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the air-assisted stretching is greater than the stretching ratio of the boric acid water stretching. By adopting such a structure, a polarizing film with acceptable optical properties can be obtained even if the total stretching ratio is small. Furthermore, the laminate is preferably provided with a drying shrinkage treatment in which the laminate is transported in the length direction while being heated so as to shrink by more than 2% in the width direction. In one embodiment, the method for manufacturing a polarizing film comprises: sequentially subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment. By introducing auxiliary stretching, the crystallinity of PVA can be improved even if PVA is coated on a thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, the problems such as the reduction and dissolution of the orientation of PVA can be prevented when immersed in water in the subsequent dyeing process and stretching process, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared with the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizing film obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved. Furthermore, by utilizing a drying shrinkage treatment to shrink the laminate in the width direction, the optical properties can be improved. The obtained laminate of the resin substrate / polarizing film can be used directly (that is, the resin substrate can be used as a protective layer of the polarizing film), or the resin substrate can be peeled off from the laminate of the resin substrate / polarizing film and any appropriate protective layer that meets the purpose can be stacked on the peeling surface and used. The details of the method for manufacturing the polarizing film will be described in item C later.

[0042] B.Polarizing plate

[0043] Figure 1 1 is a schematic cross-sectional view of a polarizing plate according to an embodiment of the present invention. The polarizing plate 100 comprises: a polarizing film 10, a first protective layer 20 disposed on one side of the polarizing film 10, and a second protective layer 30 disposed on the other side of the polarizing film 10. The polarizing film 10 is the polarizing film of the present invention described in the above-mentioned item A. One of the first protective layer 20 and the second protective layer 30 may be omitted. It should be noted that, as described above, one of the first protective layer and the second protective layer may be a resin substrate used in the manufacture of the above-mentioned polarizing film.

[0044] The first and second protective layers are formed by any appropriate film that can be used as a protective layer of a polarizing film. For the specific example of the material as the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic acid resins, acetate resins, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic acid resins, carbamate resins, (meth) acrylic acid carbamate resins, epoxy resins, and silicone resins can also be listed. In addition, for example, glassy polymers such as siloxane polymers can also be listed. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The polymer film can be, for example, an extrusion molding of the above resin composition.

[0045] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (outer protective layer) disposed on the side opposite to the display panel is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. It should be noted that, when the surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.

[0046] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (inner protective layer) disposed on the display panel side is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 60 μm. In one embodiment, the inner protective layer is a phase difference layer having any appropriate phase difference value. In this case, the in-plane phase difference Re (550) of the phase difference layer is, for example, 110 nm to 150 nm. "Re (550)" is the in-plane phase difference measured at 23 ° C with light of a wavelength of 550 nm, and is calculated by the formula: Re = (nx-ny) × d. Here, "nx" is the refractive index in the direction where the refractive index in the plane is the largest (ie, the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (film).

[0047] C. Method for manufacturing polarizing film

[0048] The manufacturing method of the polarizing film of one embodiment of the present invention comprises: forming a polyvinyl alcohol resin layer (PVA resin layer) containing a halide and a polyvinyl alcohol resin (PVA resin) on one side of a long thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment and a drying shrinkage treatment, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%. The content of the halide in the PVA resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin. The drying shrinkage treatment is preferably performed using a heating roller, and the temperature of the heating roller is preferably 60°C to 120°C. The shrinkage rate of the laminate in the width direction caused by the drying shrinkage treatment is preferably more than 2%. According to such a manufacturing method, the polarizing film described in the above-mentioned item A can be obtained. In particular, by preparing a laminate having a PVA-based resin layer containing a halide, stretching the laminate through a multi-stage stretching process including auxiliary stretching in the air and stretching in water, and heating the stretched laminate with a heating roller, a polarizing film having excellent optical properties (representatively, monomer transmittance and unit absorbance) can be obtained.

[0049] C-1. Preparation of laminate

[0050] As a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer, any appropriate method may be adopted. Preferably, a coating solution containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate and dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0051] As a coating method of the coating liquid, any appropriate method can be adopted. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.) and the like can be listed. The coating and drying temperature of the above-mentioned coating liquid is preferably 50° C. or above.

[0052] The thickness of the PVA resin layer is preferably 2 μm to 30 μm, more preferably 2 μm to 20 μm. By making the thickness of the PVA resin layer before stretching very thin and reducing the total stretching ratio as described below, a polarizing film that takes into account isotropic shrinkage and acceptable monomer transmittance and polarization degree can be obtained.

[0053] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment), or an easy-adhesive layer may be formed on the thermoplastic resin substrate. By carrying out such a treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0054] C-1-1. Thermoplastic resin substrate

[0055] As the thermoplastic resin substrate, any appropriate thermoplastic resin film may be used. Details of the thermoplastic resin substrate are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580. The entire contents of the publication are incorporated herein by reference.

[0056] C-1-2. Coating liquid

[0057] The coating liquid contains a halide and a PVA-based resin as described above. The coating liquid is typically a solution in which the halide and the PVA-based resin are dissolved in a solvent. As the solvent, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine can be cited. These can be used alone or in combination of two or more. Among these, water is preferred. The PVA-based resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. At such a resin concentration, a uniform coating film that is closely attached to the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0058] The coating liquid may be mixed with additives. As additives, for example, plasticizers, surfactants, etc. may be cited. As plasticizers, for example, polyols such as ethylene glycol and glycerol may be cited. As surfactants, for example, nonionic surfactants may be cited. These may be used for the purpose of further improving the uniformity, dyeability, and stretchability of the obtained PVA-based resin layer.

[0059] As the above-mentioned PVA-based resin, any appropriate resin can be used. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be listed. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be calculated according to JIS K 6726-1994. By using a PVA-based resin with such a saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, there is a concern that gelation will occur. As described above, the PVA-based resin preferably includes a PVA-based resin modified with an acetoacetyl group.

[0060] The average polymerization degree of the PVA-based resin can be appropriately selected depending on the purpose. The average polymerization degree is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average polymerization degree can be determined in accordance with JIS K 6726-1994.

[0061] As the above-mentioned halide, any appropriate halide can be used. For example, iodide and sodium chloride can be listed. As the iodide, for example, potassium iodide, sodium iodide, and lithium iodide can be listed. Among these, potassium iodide is preferred.

[0062] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA resin. If the amount of the halide exceeds 20 parts by weight, the halide may bleed out, and the resulting polarizing film may become cloudy.

[0063] Generally, by stretching the PVA resin layer, the orientation of the polyvinyl alcohol molecules in the PVA resin will become higher, but if the stretched PVA resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules is sometimes disordered and the orientation is reduced. In particular, when a laminate of a thermoplastic resin and a PVA resin layer is stretched in boric acid water, in order to stabilize the stretching of the thermoplastic resin, when the laminate is stretched in boric acid water at a relatively high temperature, the tendency for the above-mentioned orientation to decrease is significant. For example, the stretching of the PVA film itself in boric acid water is usually carried out at 60°C, while the stretching of the laminate of A-PET (thermoplastic resin substrate) and the PVA resin layer is carried out at a high temperature of about 70°C. In this case, the orientation of the PVA at the initial stage of stretching will decrease in the stage before it rises by stretching in water. In this regard, by preparing a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate, and performing high-temperature stretching (auxiliary stretching) in air before stretching the laminate in boric acid water, the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizing film obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved.

[0064] C-2. Aerial assisted stretching treatment

[0065] In particular, in order to obtain high optical properties, a two-stage stretching method combining dry stretching (auxiliary stretching) and boric acid water stretching is preferred. By introducing auxiliary stretching as in the two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when PVA-based resin is applied to a thermoplastic resin substrate, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, it is necessary to lower the coating temperature compared to the case where PVA-based resin is usually applied on a metal roller. As a result, the crystallization of the PVA-based resin becomes relatively low and the problem of insufficient optical properties can be obtained. In response to this, by introducing auxiliary stretching, even when PVA-based resin is applied to a thermoplastic resin, the crystallinity of the PVA-based resin can be improved, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA-based resin in advance, when immersed in water in subsequent dyeing processes and stretching processes, the problems of reduction and dissolution of the orientation of the PVA-based resin can be prevented, and high optical properties can be achieved.

[0066] The stretching method of aerial auxiliary stretching can be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rollers with different circumferential speeds). In order to obtain high optical properties, free-end stretching can be actively adopted. In one embodiment, the aerial stretching process includes a heating roller stretching process, and the heating roller stretching process is stretched by transporting the above-mentioned laminate along its length direction while utilizing the circumferential speed difference between the heating rollers. The aerial stretching process typically includes a regional stretching process and a heating roller stretching process. It should be noted that the order of the regional stretching process and the heating roller stretching process is not limited, and the regional stretching process can be performed first, or the heating roller stretching process can be performed first. The regional stretching process can also be omitted. In one embodiment, the regional stretching process and the heating roller stretching process are performed sequentially. In addition, in another embodiment, in the tenter stretching machine, stretching is performed by holding the end of the film and expanding the distance between the tenters along the flow direction (the expansion of the distance between the tenters is the stretching ratio). At this time, the distance between the tenters in the width direction (perpendicular to the flow direction) is set in an arbitrarily close manner. It is preferred to set the stretch ratio in the flow direction in a manner closer to free-end stretching. In the case of free-end stretching, the shrinkage ratio in the width direction = (1 / stretch ratio) 1 / 2 to calculate.

[0067] The auxiliary stretching in the air can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio is the product of the stretching ratios of each stage. The stretching direction in the auxiliary stretching in the air is preferably substantially the same as the stretching direction in the underwater stretching.

[0068] The stretching ratio in the air-assisted stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. When the stretching ratio of the air-assisted stretching is in such a range, the total stretching ratio can be set to the desired range when combined with the water stretching, and the desired isotropic shrinkage can be achieved. As a result, a polarizing film in which the warping in the absorption axis direction is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the air-assisted stretching is greater than the stretching ratio of the boric acid water stretching. By adopting such a structure, even if the total stretching ratio is small, a polarizing film with acceptable optical properties can be obtained.

[0069] The stretching temperature of the aerial auxiliary stretching can be set to any appropriate value according to the forming material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate + 10 ° C, and particularly preferably above Tg + 15 ° C. On the other hand, the upper limit of the stretching temperature is preferably 170 ° C. By stretching at such a temperature, the crystallization of the PVA-based resin can be suppressed from proceeding rapidly, thereby suppressing the adverse conditions caused by the crystallization (for example, hindering the orientation of the PVA-based resin layer caused by stretching).

[0070] C-3. Insolubilization, dyeing and cross-linking

[0071] As needed, an insolubilization treatment is performed after the auxiliary stretching treatment in the air and between the stretching treatment in the water and the dyeing treatment. The above-mentioned insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. The above-mentioned dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). As needed, a cross-linking treatment is performed after the dyeing treatment and before the stretching treatment in the water. The above-mentioned cross-linking treatment is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. Details about the insolubilization treatment, the dyeing treatment and the cross-linking treatment are recorded, for example, in Japanese Patent Gazette No. 2012-73580 (mentioned above).

[0072] C-4. Underwater stretching

[0073] The underwater stretching treatment is performed by immersing the laminate in a stretching bath. Through the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate and the PVA resin layer, and the PVA resin layer can be stretched while suppressing crystallization. As a result, a polarizing film with excellent optical properties can be manufactured.

[0074] The stretching method of the laminate can adopt any appropriate method. Specifically, it can be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing the laminate between rollers with different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the total ratio of stretching is the product of the stretching ratios of each stage.

[0075] The underwater stretching is preferably performed by immersing the laminate in a boric acid aqueous solution (boric acid underwater stretching). By using a boric acid aqueous solution as a stretching bath, the PVA-based resin layer can be given rigidity that can withstand the tension applied during stretching and water resistance that is insoluble in water. Specifically, boric acid generates tetrahydroxyborate anions in an aqueous solution and cross-links with the PVA-based resin through hydrogen bonds. As a result, the PVA-based resin layer can be given rigidity and water resistance so that it can be stretched well, and a polarizing film with excellent optical properties can be manufactured.

[0076] The above-mentioned boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher characteristics can be manufactured. It should be noted that an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent other than boric acid or a borate can also be used.

[0077] It is preferred to mix an iodide in the stretching bath (boric acid aqueous solution). By mixing an iodide, the dissolution of iodine adsorbed on the PVA-based resin layer can be suppressed. Specific examples of iodide are as described above. The concentration of iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight relative to 100 parts by weight of water.

[0078] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, it is possible to stretch at a high ratio while suppressing the dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably above 60°C in terms of its relationship with the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a concern that stretching cannot be performed well even if the plasticization of the thermoplastic resin substrate brought about by water is taken into account. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer becomes, and there is a concern that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0079] The stretching ratio based on underwater stretching is preferably 1.0 to 3.0 times, more preferably 1.0 to 2.0 times, and further preferably 1.0 to 1.5 times. When the stretching ratio in the underwater stretching is in such a range, the total stretching ratio can be set to the desired range, and the desired isotropic shrinkage can be achieved. As a result, a polarizing film in which the warping in the absorption axis direction is suppressed can be obtained. The total stretching ratio (the sum of the stretching ratios when the air auxiliary stretching and the water stretching are combined) is as described above, for example, 3.0 to 4.5 times, preferably 3.0 to 4.0 times, and more preferably 3.0 to 3.5 times, relative to the original length of the laminate. By adding a halide to the coating solution, adjusting the stretching ratios of the air auxiliary stretching and the water stretching, and appropriately combining the drying shrinkage treatment, even with such a total stretching ratio, a polarizing film with acceptable optical properties can be obtained.

[0080] C-5. Drying shrinkage treatment

[0081] The above-mentioned drying shrinkage treatment can be carried out by heating the region as a whole, or by heating the conveying roller (using the so-called heating roller) (heating roller drying method). It is preferred to use both of them. By using a heating roller for drying, the heating curling of the laminate can be effectively suppressed to manufacture a polarizing film with excellent appearance. Specifically, by drying the laminate along the heating roller, the crystallization of the above-mentioned thermoplastic resin substrate can be effectively promoted to increase the crystallinity, even if it is a lower drying temperature, the crystallinity of the thermoplastic resin substrate can be well increased. As a result, the rigidity of the thermoplastic resin substrate increases, thereby becoming a state that can withstand the shrinkage of the PVA-based resin layer caused by drying, and curling (warping) can be suppressed. In addition, by using a heating roller, the laminate can be dried while maintaining a flat state, so it is not only possible to suppress curling, but also to suppress the generation of wrinkles. At this time, the laminate is shrunk in the width direction by the drying shrinkage treatment, thereby improving the optical properties. This is because the orientation of PVA and PVA / iodine complex can be effectively improved. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.

[0082] Figure 2 Schematic diagram showing an example of drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by the transport rollers R1 to R6 and the guide rollers G1 to G4 heated to a predetermined temperature. In the example shown in the figure, the transport rollers R1 to R6 are arranged in a manner to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rollers R1 to R6 may be arranged in a manner to continuously heat only one surface of the laminate 200 (for example, the surface of the thermoplastic resin substrate).

[0083] The drying conditions can be controlled by adjusting the heating temperature of the conveying roller (the temperature of the heating roller), the number of heating rollers, the contact time with the heating roller, etc. The temperature of the heating roller is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. An optical laminate can be manufactured that can well increase the crystallinity of the thermoplastic resin, thereby well suppressing curling, and has very excellent durability. It should be noted that the temperature of the heating roller can be measured by a contact thermometer. Six conveying rollers are provided in the example shown in the figure, but there is no particular limitation as long as there are multiple conveying rollers. Conveying rollers are usually provided in 2 to 40 numbers, preferably 4 to 30 numbers. The contact time (total contact time) between the laminate and the heating roller is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and more preferably 1 to 10 seconds.

[0084] The heating roller can be set in a heating furnace (such as an oven) or in a normal production line (under room temperature environment). It is preferably set in a heating furnace equipped with air supply means. By combining the drying based on the heating roller and the hot air drying, the rapid temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of the hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10m / s to 30m / s. It should be noted that the wind speed is the wind speed in the heating furnace and can be measured by a mini blade type digital anemometer.

[0085] C-6. Other treatments

[0086] It is preferred that a cleaning treatment be performed after the underwater stretching treatment and before the drying shrinkage treatment. The cleaning treatment is typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0087] Example

[0088] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.

[0089] (1) Thickness

[0090] The measurement was performed using an interferometer film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name: "MCPD-3000").

[0091] (2) Shrinkage rate S MD and S TD

[0092] The polarizing films obtained in the examples and comparative examples were cut into squares of 10 cm in the absorption axis direction and 10 cm in the transmission axis direction as test samples. The precise dimensions of the absorption axis direction and the transmission axis direction of the test samples were measured using a "CNC image measuring instrument" manufactured by Mitutoyo Co., Ltd., and each dimension was designated as S. MD0 and S TD0 After measuring the dimensions, the test sample was heated at 85°C for 120 hours, and the dimensions after heating were measured in the same manner. The dimensions after heating were designated as S MD1 and S TD1 . Shrinkage rate S in the absorption axis direction MD By (S MD0 -S MD1 ) / S MD0 × 100. The shrinkage rate S in the transmission axis direction TD By (S TD0 -S TD1 ) / S TD0 × 100. According to the obtained S MD and S TD Calculate S MD / S TD .

[0093] (3) Single-body transmittance and polarization

[0094] For the laminate (polarizing plate) of the polarizing film / protective layer obtained in the examples and comparative examples, the monomer transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer ("V-7100" manufactured by JASCO Corporation) are respectively used as Ts, Tp, and Tc of the polarizing film. These Ts, Tp, and Tc are Y values ​​obtained by measuring the 2-degree field of view (C light source) of JIS Z 8701 and correcting the visual sensitivity. It should be noted that the refractive index of the protective layer is 1.50 or 1.53, and the refractive index of the surface of the polarizing film on the opposite side of the protective layer is 1.53.

[0095] The polarization degree P is calculated from the obtained Tp and Tc by the following formula.

[0096] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0097] Note that, similar measurements can be performed using a spectrophotometer such as "LPF-200" manufactured by Otsuka Electronics Co., Ltd., and it was confirmed that similar measurement results can be obtained using any spectrophotometer.

[0098] (4) Panel warping

[0099] The laminate (polarizing plate) of the polarizing film / protective layer obtained in the examples and comparative examples was bonded to a thin glass plate (thickness 0.1 mm) as a sample corresponding to an image display panel. The sample corresponding to the image display panel was subjected to a heating test at 80°C for 24 hours, and the warpage after the test was measured. The average of the warpage of the four corners of the sample corresponding to the image display panel was taken as the warpage of the panel, and the evaluation was performed according to the following criteria.

[0100] ○: Warping is less than 4 mm

[0101] ×: Warpage is 4 mm or more

[0102] (5) Bending test

[0103] The laminate (polarizing plate) of the polarizing film / protective layer obtained in the examples and comparative examples was cut into a size of 120 mm (absorption axis direction of the polarizing film) × 30 mm (direction orthogonal to the absorption axis direction of the polarizing film) as a measurement sample. A continuous bending test was performed on the measurement sample using a continuous bending test device in a no-load U-shaped telescopic mode (manufactured by YUASA SYSTEM Co., Ltd., product name "DLDMLH-FS"). The bending speed was 60 rpm, the bending amplitude was 20 mm, the bending radius of curvature was 1.0 mm, and the number of bendings was 100,000 times. Evaluation was performed according to the following criteria.

[0104] ○: No crease was observed

[0105] ×: Creases are observed

[0106] [Example 1]

[0107] As the thermoplastic resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate film (thickness: 100 μm) with a water absorption of 0.75% and a Tg of about 75°C was used. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W·min / m 2 ).

[0108] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1 to prepare a PVA aqueous solution (coating solution).

[0109] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a 13 μm-thick PVA-based resin layer, thereby producing a laminate.

[0110] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds in an oven at 130° C. (in-air auxiliary stretching treatment).

[0111] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0112] Next, the film was immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds (dyeing treatment) at a concentration adjusted so that the single body transmittance (Ts) of the finally obtained polarizing film would be 41.0%.

[0113] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0114] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4.0 wt %, potassium iodide: 5.0 wt %) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (length direction) between rollers having different circumferential speeds to a total stretching ratio of 3.0 times (underwater stretching treatment: the stretching ratio in the underwater stretching treatment was 1.25 times).

[0115] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0116] Thereafter, the laminate was brought into contact with a SUS heating roll having a surface temperature of 75° C. for about 2 seconds while being dried in an oven maintained at 90° C. (drying shrinkage treatment). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 2%.

[0117] In this manner, a polarizing film having a thickness of 6.8 μm was formed on the resin substrate.

[0118] An unstretched cycloolefin film (ZEONOR FILM: ZF14 manufactured by Zeon Corporation, with a surface refractive index of 1.53 and a thickness of 25 μm) is bonded as a protective film to the surface of the polarizing film obtained above (the surface on the opposite side to the resin substrate) with the aid of an ultraviolet curing adhesive. Specifically, the curing adhesive is applied in such a manner that the total thickness is 1.0 μm, and a roller press is used for bonding. Thereafter, the adhesive is cured by irradiating UV light from the protective film side. Next, the resin substrate is peeled off to obtain a polarizing plate having a structure of a protective film / polarizing film. For the polarizing plate obtained above, an adhesive having a creep amount of 70 μm / h when loaded with a load of 500 g for 1 hour is bonded to the surface of the polarizing film from which the resin substrate is peeled off to obtain a polarizing plate with an adhesive layer (protective film / polarizing film / adhesive layer).

[0119] For the obtained polarizing film or polarizing plate, S MD , S TD and S MD / S TD , single body transmittance, polarization degree, and the results of warping and bending tests are shown in Table 1.

[0120] [Example 2]

[0121] A polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Example 1 except that an obliquely stretched cycloolefin film (ZEONOR FILM: ZD12 manufactured by Zeon Corporation, surface refractive index 1.53, thickness 25 μm) was used as a protective film. The obtained polarizing film or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0122] [Example 3]

[0123] A polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Example 1 except that a 20 μm-thick acrylic film was used as the protective film. The obtained polarizing film or polarizing plate was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0124] [Example 4]

[0125] A polarizing film having a thickness of 6.4 μm was prepared in the same manner as in Example 1 except that the stretching ratio in the underwater stretching treatment was set to 1.45 times and the total stretching ratio was set to 3.5 times. The polarizing film was used, and a polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Example 3 except that the polarizing film was used. The obtained polarizing film or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0126] [Example 5]

[0127] A polarizing film having a thickness of 5.9 μm was prepared in the same manner as in Example 1 except that the stretching ratio in the underwater stretching treatment was set to 1.67 times and the total stretching ratio was set to 4.0 times. The polarizing film was used, and a polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Example 3 except that the polarizing film was used. The obtained polarizing film or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0128] [Comparative Example 1]

[0129] A polarizing film having a thickness of 5.0 μm was prepared in the same manner as in Example 1 except that the stretching ratio of the underwater stretching treatment was set to 2.4 times, the total stretching ratio was set to 5.5 times, and the liquid temperature of the stretching bath was set to 70° C. A polarizing film having a thickness of 5.0 μm was prepared. A polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Example 1 except that the polarizing film was used. The obtained polarizing film or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0130] [Comparative Example 2]

[0131] A polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Comparative Example 1 except that an obliquely stretched cycloolefin film was used as the protective film. The obtained polarizing film or polarizing plate was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0132] [Comparative Example 3]

[0133] A polarizing plate and a polarizing plate with an adhesive layer were prepared in the same manner as in Comparative Example 1 except that an acrylic resin film was used as the protective film. The obtained polarizing film or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0134] [Comparative Example 4]

[0135] A long roll of a PVA resin film (manufactured by KURARAY CO., LTD, product name "PE3000") with a thickness of 30 μm was uniaxially stretched along the long side direction with a roller stretching machine in a manner that the total stretching ratio is 6.0 times, and swelling, dyeing, cross-linking and cleaning treatments were simultaneously performed, and finally a drying treatment was performed to prepare a polarizer with a thickness of 12 μm. A polarizing plate was prepared by bonding an obliquely stretched cycloolefin film to one side of the polarizer. Furthermore, using this polarizing plate, except for this, a polarizing plate with an adhesive layer was prepared in the same manner as in Example 1. The obtained polarizer or polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0136] [Comparative Example 5]

[0137] A polarizer with a thickness of 17 μm was prepared in the same manner as in Comparative Example 4 except that the total stretching ratio was set to 3.0 times. A polarizer and a polarizer with an adhesive layer were prepared in the same manner as in Example 1 except that the polarizer was used. The obtained polarizer or polarizer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0138] [Table 1]

[0139]

[0140] As is clear from Table 1, the polarizing films of Examples of the present invention have suppressed warping and have excellent bendability.

[0141] Industrial Applicability

[0142] The polarizing film and polarizing plate of the present invention are suitable for use in liquid crystal display devices.

[0143] Description of Reference Numerals

[0144] 10 polarizing film

[0145] 201st protection layer

[0146] 30Second protection layer

[0147] 100 polarizing plates

Claims

1. A method for manufacturing a polarizing plate, the polarizing plate comprising: a polarizing film, and a protective layer disposed on at least one side of the polarizing film, The polarizing film is composed of a polyvinyl alcohol-based resin film containing a dichroic substance, has a thickness of 8 μm or less, a single body transmittance of 41.0% or more, and a polarization degree of 99.4% to 99.99%. In the polarizing plate, the shrinkage rate S in the absorption axis direction of the polarizing film after being left at 85° C. for 120 hours is MD The shrinkage rate S in the direction perpendicular to the absorption axis direction TD The ratio of S MD / S TD 0.94~1.16, The manufacturing method comprises: A polyvinyl alcohol-based resin layer containing iodide or sodium chloride and polyvinyl alcohol-based resin is formed on one side of a long thermoplastic resin substrate to prepare a laminate; and subjecting the laminate to an aerial auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in sequence, wherein the drying shrinkage treatment is performed by heating the laminate while conveying the laminate in the length direction, thereby shrinking the laminate in the width direction by more than 2%, The total stretching ratio of the auxiliary in-air stretching treatment and the underwater stretching treatment is 3.0 to 3.5 times the original length of the laminate. The stretching ratio of the in-air auxiliary stretching treatment is greater than the stretching ratio of the underwater stretching treatment.

2. The manufacturing method according to claim 1, wherein: The orientation function of the polarizing film is less than or equal to 0.

30.

3. The manufacturing method according to claim 1 or 2, wherein: The stretching ratio of the auxiliary stretching treatment in the air is 2.0 to 3.0 times, and the stretching ratio of the underwater stretching treatment is 1.0 to 1.5 times.

Citation Information

Patent Citations

  • Polarizing plate

    TW201905497A